The virtual world and the birth of a new human - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2023)
The process of transformation of virtual space, as well as its impact on a person, is being investigated. The problems of the formation of a new architecture of modern society, global virtualisation of the world, as well as the growth of social atomisation are revealed. Changes in the interrelations of individuals caused by the renewal of the human life activity system are shown. It is noted that the introduction of global digital technologies and communication systems into everyday life changes a person’s potential, the formation of a virtual cluster in society triggers the process of modernising life. The mechanisms of reconstructing the sociocultural architecture of society are considered. It is concluded that any progress in the life of society should be accompanied by a spiritual renewal of a person, a change in his values, taking into account national traditions and historical experience. It is noted that in the modern virtual world, a person is being formed with new value orientations, a new understanding of good and evil, a new view of the future.
Keywords: new human; modern society; virtual world; social atomisation; virtual culture; values